Appraising the Poetic Power of Children's Video Games. Issue 1 (July 2018) - Reay, Emma
Abstract : To date, most studies of video games by children's literature scholars have been 'child-oriented' rather than 'text-oriented', focusing on the needs and capabilities of child-players rather than on the literary and artistic potential of the games themselves. This essay proposes that in-depth textual analyses of children's video games will not only illuminate the aesthetic value of specific texts, but also refashion and redirect scholarly debate about the medium itself. What is more, an open dialogue between games scholarship and children's literature scholarship is likely to yield the kind of rich, flexible and nuanced critical discourse necessary to navigate a rapidly evolving, increasingly diverse children's media ecology. Here the case is made for both a strong interdisciplinary alliance between children's literature scholarship and games scholarship, and for modelling a style of close reading that attends specifically to the visual, auditory, tactile and performative elements of children's video games. This method of close reading is called 'critical ekphrasis', where 'ekphrasis' denotes the careful and creative transcription of the supralinguistic, non-verbal signifiers of video games for the purpose of critical analysis. Critical ekphrasis is offered as a bridge between disciplines that enables children's literature scholars to bring their unique expertise to bear on the complex, varied and exciting body of texts that constitutes 'children's video games'.